Analysis of the Structural Response of a 2919 GT Ro-Ro Ship Due to Changes in Hull Construction Length - Mulyatno, Imam Pujo; Zakki, Ahmad Fauzan; Wicaksono, Kukuh Prakoso; Adietya, Berlian Arswendo; Tuswan, Tuswan (Institut Teknologi Sepuluh Nopember, 2024)
On the 2919 GT Ro-Ro vessel, structural geometry changes, specifically in the Length Between Perpendiculars (LPP) with additional framing, lead to variations in loading and maximum stress, in accordance with Biro Klasifikasi Indonesia (BKI) regulations in Volume II. Finite Element Method analysis reveals structural responses, particularly in the parallel middle body section. Initially, the vessel was 10.5 meters long to support loads of seven 20-foot trucks; modifications increased this to 13.5 meters for loads of seven 40-foot trucks and 18 meters for a combination of 20-foot and 40-foot truck loads. The analysis results indicate significant differences in the vessel’s maximum structural stress under truck-loaded conditions. For lengths of 10.5 meters, 13.5 meters, and 18 meters, the stresses remain within safe limits under all conditions (Calm Water, Sagging, and Hogging), with σult lower than the allowable as set by BKI. However, the 18-meter length exhibits maximum stress approaching the safe threshold in the Hogging condition, with σult = reaching 243.4 MPa, suggesting structural modifications are required to ensure vessel safety.